2020
DOI: 10.9734/ijtdh/2020/v41i2430421
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spleen Stiffness for Prediction of Varices in Patients with Hepatitis C Related Cirrhosis Using Transient Elastography

Abstract: Background and Study Aims: Portal hypertension is one of the most important complications of liver cirrhosis. The prevalence of varices among cirrhotic patients is variable. Therefore, endoscopic screening of all patients with liver cirrhosis would result in a large number of unnecessary additional burdens to endoscopic units. Our aim was to assess the diagnostic accuracy of spleen stiffness measured by transient elastography (Fibroscan) for prediction of the presence of varices in patients with hepatitis C re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The assessment of liver stiffness showed statistically significant lower results in the group without varices than in the LRV group (24.9 ± 2.7 kpa and 29.4 ± 5.5 kpa, respectively), and in the LRV group (29.4 ± 5.5 kpa) than in the HRV group (38.6 ± 9.26 kpa). This is consistent with El-Toukhy et al (21) findings, which showed that patients with EV had considerably greater liver stiffness measurements than patients without varices; at the cutoff (≥28 kpa), the test had 63.4% sensitivity and 100% specificity in EV prediction.…”
Section: Discussionsupporting
confidence: 90%
“…The assessment of liver stiffness showed statistically significant lower results in the group without varices than in the LRV group (24.9 ± 2.7 kpa and 29.4 ± 5.5 kpa, respectively), and in the LRV group (29.4 ± 5.5 kpa) than in the HRV group (38.6 ± 9.26 kpa). This is consistent with El-Toukhy et al (21) findings, which showed that patients with EV had considerably greater liver stiffness measurements than patients without varices; at the cutoff (≥28 kpa), the test had 63.4% sensitivity and 100% specificity in EV prediction.…”
Section: Discussionsupporting
confidence: 90%